Escherichia coli supH suppressor: temperature-sensitive missense suppression caused by an anticodon change in tRNASer2. - Thorbjarnardóttir, S (1985)
We describe the cloning and the DNA sequence of the Escherichia coli supH missense suppressor and of the supD60(Am) suppressor genes. supH is a mutant form of serU which codes for tRNASer2. The supH coding sequence differs from the wild-type sequence by a single nucleotide change which corresponds to the middle position of the anticodon. The CGA anticodon of wild-type tRNA and CUA anticodon of supD tRNA is changed to CAA in supH tRNA, which is expected to recognize the UUG leucine codon. We propose that the supH suppressor causes the insertion of serine in response to this codon. The temperature sensitivity caused by supH may be due to a conformation of the CAA anticodon in the supH tRNASer that is slightly different than that in the corresponding tRNALeu species.